THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE WITH GIVING VITAMIN A CAPSULES TO POSTPARTUM MOTHERS IN THE TANJUNG MARULAK HEALTH CENTER WORK AREA, TEBING TINGGI CITY IN 2023 - Helti, Mestika Riza; Wahyuni, Faradita (International Archives of Medical Sciences and Public Health, 2025)
Menstruation is a significant occurrence in the life of a young woman. Certain adolescents may encounter disruptions during menstruation, specifically experiencing discomfort during menstruation (dysmenorrhea). The management of menstrual pain is categorized into two distinct approaches: pharmacological and non-pharmacological. Carrot juice is a non-pharmacological treatment option. The objective of this study is to assess the impact of administering carrot juice (daucus carota) on alleviating dysmenorrhea pain among female students at SMP Negeri 10 Tebing Tinggi City in 2022. The research method employed in this study is a quasi-experiment utilizing a one-group pretest-posttest design. The study encompassed the entire population of 93 class IX students at SMP Negeri 10 Tebing Tinggi City. The sampling technique employed the Lemeshow formula with a sample size of 15 individuals. The sampling method employed is purposive sampling. The data utilized consists of primary and secondary data, which were gathered through observation sheets. Subsequently, the data was processed and analyzed employing the paired t-test method. The findings indicated that the pretest group predominantly experienced moderate dysmenorrhea pain, with a total of 11 individuals (73.3%). Following the administration of carrot juice, dysmenorrheal pain decreased to mild pain in 12 individuals (80.0%). The statistical test yielded a p-value of 0.000. Conclusion: Carrot juice (daucus carota) has been found to have a positive impact on reducing dysmenorrhoea pain. Therefore, young women can utilize carrots as a non-pharmacological and easily accessible method to alleviate menstrual pain.